Catechin from Avocado Seed (Persea Americana Mill.) Potentially Targets Estrogen Receptor-Alpha: Computational-Based Analysis - Martiza Aulia; Fahrana Rosani; Tarisa Nurafni Romadhona; Lintang Gusti Kinanti; Kevin Gabriel; Agus Rusdin; Dhania Novitasari (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Avocado seeds (Persea americana Mill.) are known to possess various pharmacological properties, including notable anticancer potential. While preliminary studies have reported the cytotoxic effects of avocado seed extracts on breast cancer cells, there is still a lack of comprehensive research exploring the underlying molecular mechanisms responsible for these effects. This study explores bioactive compounds found in avocado seeds as potential agents targeting estrogen receptor alpha (ERα), a key biomarker in breast and cervical cancers. The investigation employs a range of computational approaches, including the Lipinski Rule of Five, ADME/Tox predictions, pharmacophore screening, and molecular docking analysis. Of the ten tested compounds, seven passed the Lipinski Rule of Five. ADME/Tox analysis revealed that most compounds exhibited adequate human intestinal absorption (HIA), poor blood-brain barrier (BBB) penetration, moderate Caco-2 permeability, and good plasma protein binding (PPB), while some were predicted to be mutagenic or carcinogenic. Pharmacophore modeling yielded an AUC of 0.87, with procyanidin B scoring 45.09 as a hit compound. Molecular docking revealed catechin, hyoscyamine, and atropine had the lowest Gibbs free energy (-5.15, -0.10, -0.07 kcal/mol). Among the compounds, catechin in avocado seed shows the highest potential for development as an ER-targeted anticancer agent.